Rural outmigration-feminization-agricultural production nexus: Case of Vietnam - Bacud, Salve (International Rice Research Institute, 2019)
Presented by Eva Salve Bacud (International Rice Research Institute), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.